2013
DOI: 10.1007/s10653-013-9518-y
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the malignant mesothelioma cases and environmental asbestos exposure in Sivas province, Turkey

Abstract: One of the most significant diseases related to environmental asbestos exposure is malignant mesothelioma (MM). Sivas province is located in the Central Anatolia where asbestos exposure is common. We aimed to study clinical, demographical and epidemiologic features of the patients with MM in Sivas, along with the history of asbestos exposure. In total, 219 patients with MM who were diagnosed in our hospital between 1993 and 2010 were retrospectively analyzed in terms of demographical and clinical features. Roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Other epidemiological risk factors, e.g. asbestos-like exposure and high arsenic level in drinking water in Turkey may also play a role in the observed high male lung cancer rate in Turkey [13,14]. However, the high lung cancer rate in men and low rate in women can be explained by the male to female ratios of lung cancer and smoking prevalence presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Other epidemiological risk factors, e.g. asbestos-like exposure and high arsenic level in drinking water in Turkey may also play a role in the observed high male lung cancer rate in Turkey [13,14]. However, the high lung cancer rate in men and low rate in women can be explained by the male to female ratios of lung cancer and smoking prevalence presented in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental exposure from naturally occurring asbestos contamination of the soil has been documented in Turkey, where mesothelioma epidemics due to the presence of tremolite, chrysotile and erionite, belonging to the zeolite family, have been proved 26. In Greece, a high frequency of pleural calcification was found in patients living in places where no industrial use of asbestos was documented in the past, but tremolite fibres have been found in the soil used to make whitewash that was commonly applied to homes in the affected areas 27.…”
Section: Discussionmentioning
confidence: 99%
“…3). The geographic locations of the studies included places where asbestos was historically used in industrial/mining activities, such as Wittenoom in West Australia [38][39][40]60 ; the Veneto region, 20,24 the Trieste-Monfalcone area, 18 Naples, 23 and the Lombardy region 28 in Italy; Thetford Mines in Quebec, Canada 58 ; and places where naturally occurring asbestos (NOA) was recognized (such as Sivas, Turkey [31][32][33]37 ; Metsovo, Greece 54 ; New Caledonia 42 ; and Biancavilla in Sicily, Italy 22 ). There are also a few relatively new locations of NOA identified in Southern Nevada 61 and Dunn County, North Dakota 63 in the United States; in Mexico 49,50 ; and in Dayao, Yunnan Province, People's Republic of China.…”
Section: Geographic Locationmentioning
confidence: 99%
“…44 A higher proportion of MM cases with nonoccupational asbestos exposure was reported in areas where NOA or other types of environmental asbestos exposure are dominant. 22,31,32,45,46 Studies on neighborhood exposures have reported that increased distance from the sources and decreased exposure duration are associated with decreased MM risk. For example, Tarrés et al 57 reported an MM incidence rate ratio (IRR) of 12.92 (95% CI: 10.77-15.33) for those living less than 500 m from an asbestos cement plant in Barcelona, Spain, whereas the ratios decreased to 0.70 and 0.23 for those living 500 to 2000 m or more than 2000 to 10,000 m from the plant, respectively.…”
Section: Incidencementioning
confidence: 99%